Pengaruh Rasio Laju Alir Gas Nitrogen-Hydrogen serta Gas Pressure pada RF Plasma Nitriding terhadap Surface Hardness Spesimen SUS304 - Oerbandono, Tjuk (Jurnal Rekayasa Mesin, 2016)
RF Plasma nitriding was done on the specimen SUS304. This research had aim to obtain a high surface hardness value as a result of flow rate ratio of Nitrogen-Hydrogen. The experimental research consisted of three models. Each experimental model used varying parameters and constant parameters. Micro Vickers Hardness test was used for testing each specimen of the experimental models. The varying parameters of first experimental model were times of plasma nitriding, ie, 1 hour, 2 hours, 4 hours and 8 hours. The constant parameters were RF-Power Voltage = 250 Volts, DC-Bias Voltage = 500 Volts, N2= 100 (ml/min), H2= 20 (ml/min), Gas pressure (P) = 70 Pa and Heater Temperature (T) = 420oC. The second experimental model contained three varying parameters of nitrogen gas pressure ie, 50 Pa, 60 Pa and 70 Pa. The constant parameters of second experimental model were time of plasma nitriding (t) = 8 Hours, RF-Power Voltage = 250 Volts, Heater Temperature (T) = 420oC, N2 = 140 (ml/min), H2= 20(ml/min). The first and second experimental models had same configuration. The third experimental model used three variations of nitrogen flow rate, ie, 140 (ml/ min), 160 (ml/min), 180 (ml/min). The constant parameters were time of plasma nitriding (t) = 4 hours, RF-Voltage = 250 volts, The Heater temperature (T) = 420oC; H2 = 20 (ml/min), DC-Bias Voltage = 500 Volts, the gas pressure (P) = 60 Pa. The configuration of third experimental model was different with the configurations in first and second experimental models. Surface hardness Values of first experimental model were 379 HV, 348 HV, 474 HV and 387 HV. Surface hardness values of second experimental model were 586 HV, 607HV, 249 HV. Surface hardness values of third experimental model were 313 HV, 574 HV, and 677 HV. from the results were known that nitrogen-hydrogen flow rate ratio into vacuum chamber and gas pressure influenced the surface hardness of SUS304 specimen. The highest surface hardness value of 677 HV was happened at gas pressure of 60 Pa, nitrogen flow rate of 180 (ml/min) and hydrogen flow rate of 20(ml/min).